Development of Geogebra-Assisted Problem Based Learning (PBL) Learning Tools to Improve Visual Thinking Skills in Mathematical Problem Solving Students of SMA Negeri 1 Samudera - Kholilah Amriani Harahap; Bornok Sinaga; Pargaulan Siagian (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This study aims to produce valid, practical, and effective learning tools, as well as to analyze the improvement of visual thinking skills in problem solving for XI grade students of SMA Negeri 1 Samudera using mathematics learning tools oriented problem based learning assisted by GeoGebra. The data were obtained through the validation sheet of teaching materials, observation sheets, student response questionnaires, and instruments for testing the ability of visual thinking in solving mathematical problems. This study uses the Dick & Carey (1996) development model. Based on the results of the validity by the validator team, the average validity of the RPP was 4.51, LKPD was 4.22, and student books were 4.29. Expert / practitioner assessment which states that learning devices can be used with a few revisions and without revision, the results of interviews with teachers and students obtain information that learning devices can be used easily and the results of observations of the implementation of learning tools in class in the first trial of 81.67% and in the second trial of 87.22% and included in the good category. Learning devices in trial II, obtaining classical student learning completeness results have been achieved in trial II, namely 87.5%, the achievement of learning objectives has been achieved for each item in trial II, student responses are very positive to the device being developed and learning time does not exceed ordinary learning, namely three meetings.